Tailoring carbon-matrix composites interfaces using reduced graphene oxide for high strength. (August 2022) - Chen, Qichen; Wei, Wenfu; Xiao, Song; Yang, Zefeng; Huang, Guizao; Li, Hao; Yin, Haojie; Lin, Jiahui; Kang, Qi; Li, Pengli; Wang, Hong; Tu, Chuanjun; et al.
Abstract: The interfacial interaction between the carbonized matrix and binder directly correlates with the performance of the carbon-matrix composites. The involvement of the reduced graphene oxide (rGO) in composites is considered an effective strategy to enhance the performance of composites via improving the interface property. Herein, the rGO was converted in-situ from the graphene oxide (GO) on the interface between the matrix and the carbonized binder during the sintering process. Compared with the pristine composites, the compressive strength (203.90 MPa ±2.85 MPa) and flexural strength (40.53 ± 1.42 MPa) of carbon-matrix composites doping 0.2 wt% of GO can be increased by 112.1% and 71.2%, respectively. It is attributed to the fact that rGO forms an ideal interface bond with the carbonized matrix and binder, which effectively promotes the deflection of the crack propagation path. Meanwhile, molecular dynamics simulations unlocked an automatic protective reinforcement mechanism of the rGO-enhanced composites. A low-cost yet effective scheme for improving composites interfaces is proposed here, which lays a theoretical foundation for developing the high-strength carbon-matrix composites. Graphical abstract: Image 1 Highlights: Reduced graphene oxide (rGO) interface engineering is explored in carbon-matrix composite material. The rGO is converted in-situ from the graphene oxide (GO) introduced by a facile shear mixing. The mechanical enhancing mechanism stems from the deflection of the crack propagation path under the effect of rGO. This efficient and low-cost strategy has a strong potential to produce high-strength carbon-matrix composites.